Fabrication and characterization of polyimide/Al2O3 composite films via surface modification and ion exchange technique. Issue 1 (4th January 2016) - Zhang, M.Y.; Liu, L.Z.; Weng, L.; Cui, W.W.; Hui, K.S.
Abstract : Purpose: – The aim of this study was to fabricate polyimide (PI)/Al2 O3 composite films via surface modification and ion exchange techniques, and examine their properties. Design/methodology/approach: – The method involves hydrolyzing the PI film double surface layers in an aqueous potassium hydroxide (KOH) solution and incorporating aluminium ions (Al3+) into the hydrolyzed layers of the PI film via subsequent ion exchange, followed by a treatment of the Al3+-loaded PI films with an aqueous ammonia solution, which leads to the formation of Al(OH)3 in the surface-modified layers. After a final thermal annealing treatment in ambient air, the Al(OH)3 decomposes to Al2 O3, and forms composite layers on both surfaces of the re-imidized PI film. Findings: – The PI/Al2 O3 composite film obtained with a 6 hours of KOH treatment exhibited excellent thermal stability, good mechanical properties and better electric breakdown strength and corona-resistance properties than the pristine PI film. Practical implications: – The method for obtaining the composite films in this paper is worth consideration, but additional research will be needed. Furthermore, this method is of general importance for the fabrication of composite PI films with tailored properties. Originality/value: – This study showed that surface modification and ion-exchange techniques are powerful methodologies for the fabrication of PI/Al2 O3 composite films.